Nutritional Safety and Health Resilience in Europe: Declining Micronutrient Intakes, Widening Distributional Disparities and Persistent Inadequacies Revealed from National Dietary Surveys - Samantha Christie; Adrian F. Gombart; Thomas R. Hill; Tao You; Philip C. Calder (Nutrients, 2026)
Background: Nutritional safety has traditionally focused on preventing excessive nutrient exposure, yet chronic micronutrient inadequacy may also impair physiological function and health resilience. As the European Commission prepares to harmonise maximum permitted levels for food supplements and fortified foods, understanding long-term population intake trends is increasingly important. We assessed changes in micronutrient intakes and adequacy among adults in four European countries. Methods: Repeated, cross-sectional, secondary analyses of published adult (≥18 years) micronutrient intakes over approximately two decades were conducted using publicly available, non-harmonised national dietary surveys at non-contemporaneous time points in the Netherlands, Ireland, France and the United Kingdom (n = 17,261). Mean, lower-tail (5th centile; UK 2.5th) and upper-tail (95th centile; UK 97.5th) intakes were evaluated against dietary reference values, and changes in population intake estimates over the past two decades were examined. Results: Intakes of several micronutrients declined substantially, with mean and lower-tail intakes of vitamins D and A, riboflavin, folate and of calcium, iron and iodine decreasing by up to 50% in some population groups, indicating widening intake disparities and increasing risk of chronic insufficiency. Although improvements in some micronutrients were consistent with fortification policies and dietary changes, inadequacies remained widespread, including for vitamin D across all countries, iron in women, potassium in UK women, selenium in most populations and copper in Irish women. Folate intake in UK women and vitamin A intake in France were marginal. Conclusions: Declining intakes of several micronutrients and persistent inadequacies indicate emerging nutritional safety concerns in Europe. Population intake trends and chronic insufficiency should be explicitly considered in nutritional safety assessments, maximum permitted level discussions and modelling and future public health policy.